2021
DOI: 10.3390/polym13224017
|View full text |Cite
|
Sign up to set email alerts
|

Development of Oil and Gas Stimulation Fluids Based on Polymers and Recycled Produced Water

Abstract: Freshwater scarcity is a highly pressing and accelerating issue facing our planet. Therefore, there is a great incentive to develop sustainable solutions by reusing wastewater or produced water (PW), especially in places where it is generated abundantly. PW represents the water produced as a by-product during oil and gas extraction operations in the petroleum industry. It is the largest wastewater stream within the industry, with hundreds of millions of produced water barrels per day worldwide. This research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…An environmentally friendly stimulation fluid has been developed by adding GLDA to polymeric gel solutions. 70 The results showed that GLDA improved the stability and viscosity of the gel solution. Additionally, another stimulation fluid was created by combining GLDA with a polymeric gel solutions.…”
Section: Chelating Agents Effects On Seawater Fluidmentioning
confidence: 96%
See 1 more Smart Citation
“…An environmentally friendly stimulation fluid has been developed by adding GLDA to polymeric gel solutions. 70 The results showed that GLDA improved the stability and viscosity of the gel solution. Additionally, another stimulation fluid was created by combining GLDA with a polymeric gel solutions.…”
Section: Chelating Agents Effects On Seawater Fluidmentioning
confidence: 96%
“…GLDA is environmentally friendly and more resistant to high temperatures and salinity. ,, Additionally, it has the ability to increase the viscosity of the stimulation fluid. An environmentally friendly stimulation fluid has been developed by adding GLDA to polymeric gel solutions . The results showed that GLDA improved the stability and viscosity of the gel solution.…”
Section: Chelating Agents Effects On Seawater Fluidmentioning
confidence: 99%